Identifikasi dan Kelimpahan Plankton di Tambak Udang Vannamei (Litopenaeus vannamei) Desa Sawojajar Kecamatan Wanasari, Kabupaten Brebes - Sri Mulatsih,; Karina Farkha Dina; Ninik Umi Hartanti; suyono; Nurjannah; Sutaman; Narto; Rosanti Diah Safitri (Universitas Sumatera Selatan, 2023)
Ponds in Indonesia, especially in Brebes district, usually produce export-oriented fishery products that have high economic value. One of the fishery products currently being developed is vannamei shrimp (Litopenaeus vannamei). The presence of plankton in the water can be used as an indicator of water quality because it is strongly influenced by water quality. The purpose of this study was to estimate the abundance and stability of pond water from biological measurements (variation, diversity, and dominance of plankton) in the Sawojajar vannamei shrimp ponds. The method used is quantitative and descriptive at random. The results showed that the value of the abundance of phytoplankton ranged from 3451 to 6895 cells/mL, with the highest relative abundance being the type of Bacillariophyta. Meanwhile, the abundance of zooplankton ranged from 45 to 525 ind/mL, with Rotifera having the highest relative abundance. The diversity index status (H') is moderate, the uniformity index (E) is high, and the dominance index is low. Phosphate and COD found were high, as were other water qualities such as DO and temperature. Optimum pH, salinity, and brightness